2017
DOI: 10.5897/ajar2017.12667
|View full text |Cite
|
Sign up to set email alerts
|

Effect of modified spacing arrangements, fertilizer use and legume intercrop on prevalence of cassava brown streak disease in Western Kenya

Abstract: Cassava is an important food security crop in Western and Coastal counties of Kenya. As a food security crop, it is continuously cultivated with minimal inputs. Its production is constrained by factors like declining soil fertility, poor agronomic practices, pests and diseases. Cassava brown streak disease (CBSD) is a viral infection attacking the cassava crop causing yield losses of up to 100%. The current study was intended to determine the effect of planting technologies on the prevalence of CBSD in two agr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Meanwhile, it was reported in [147] that pest and disease attacks could be reduced by 73% with mixed-crop planting. A more recent study found that an intercropping system with legumes in western Kenya suppressed brown line disease in cassava [148]. The intensity of pest damage in AF systems is lower than in monoculture agriculture [149], because AF planting patterns affect pests and diseases not only based on the plant species, but also other factors, including pest types, pest preferences, and microclimate [150,151].…”
Section: Use Of Biofertilizers In Agroforestrymentioning
confidence: 99%
“…Meanwhile, it was reported in [147] that pest and disease attacks could be reduced by 73% with mixed-crop planting. A more recent study found that an intercropping system with legumes in western Kenya suppressed brown line disease in cassava [148]. The intensity of pest damage in AF systems is lower than in monoculture agriculture [149], because AF planting patterns affect pests and diseases not only based on the plant species, but also other factors, including pest types, pest preferences, and microclimate [150,151].…”
Section: Use Of Biofertilizers In Agroforestrymentioning
confidence: 99%
“…Cultural differences in crops grown by men and women have been sufficiently thought of (Anderson et al, 2021;Ankrah et al, 2020;Michels et al, 2019;Pawlak and Kołodziejczak, 2020;Akter et al, 2017). Cassava (Manihot esculentum Crantz) is an important food security crop that is cultivated with minimal inputs in Western and Coastal counties of Kenya (Ememwa et al, 2017), and a thorough comprehension of the processes associated with its production among smallholder women and men farmers, especially in Rongo Sub County in Migori County of Kenya. This is completely fitting especially Kenya when the government industriously strives to realisation of Sustainable Development Goal (SDG) 5 and Vision 2030 that focus on gender equality.…”
Section: Introductionmentioning
confidence: 99%